2009
DOI: 10.1007/s12015-009-9094-9
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cell Marker Expression Pattern in Human Mesenchymal Stem Cells Derived from Bone Marrow, Adipose Tissue, Heart and Dermis

Abstract: Mesenchymal stem cells (MSCs) have been isolated from a variety of human tissues, e.g., bone marrow, adipose tissue, dermis, hair follicles, heart, liver, spleen, dental pulp. Due to their immunomodulatory and regenerative potential MSCs have shown promising results in preclinical and clinical studies for a variety of conditions, such as graft versus host disease (GvHD), Crohn's disease, osteogenesis imperfecta, cartilage damage and myocardial infarction. MSC cultures are composed of heterogeneous cell populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
164
2
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(205 citation statements)
references
References 31 publications
30
164
2
7
Order By: Relevance
“…It is also difficult to obtain adult stem cells because of their limited quantities in the tissue. According to some previous literatures, they are considered to be composed of 0.01% to 0.001% of the total cell number (Hill et al, 2012;Rendl et al, 2005;Riekstina et al, 2009;Shim et al, 2013;Wegner and Stolt, 2005;Wu et al, 2010). We found that hDSPCs in small quantity gradually lose pluripotency and the ability to proliferate once they are grown over long-term culture.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is also difficult to obtain adult stem cells because of their limited quantities in the tissue. According to some previous literatures, they are considered to be composed of 0.01% to 0.001% of the total cell number (Hill et al, 2012;Rendl et al, 2005;Riekstina et al, 2009;Shim et al, 2013;Wegner and Stolt, 2005;Wu et al, 2010). We found that hDSPCs in small quantity gradually lose pluripotency and the ability to proliferate once they are grown over long-term culture.…”
Section: Introductionmentioning
confidence: 80%
“…SOX2, a SRY transcription factor, plays an essential role in maintaining stemness in embryonic stem cells and some adult stem cells such as the dermal papilla cells (Rendl et al, 2005;Wegner and Stolt, 2005). NANOG, another embryonic stem cell marker, is also expressed in adult mesenchymal stem cell populations derived from bone marrow, adipose tissue, and dermis (Hill et al, 2012;Riekstina et al, 2009;Szade et al, 2011). S100B are known to be specifically upregulated in dermal stem cells (Driskell et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…VI (4) VII (19) VIII (20,21) IX (3,(22)(23)(24)(25) X (4) XI (3,(22)(23)(24)(25) XII (3,(22)(23)(24)(25) XIII ( (17) IV (4) V (4,18) VI (4) VII (19) VIII (20,21) IX (3,(22)(23)(24)(25) X (4) XI (3,(22)(23)(24)(25) XII (3,(22)(23)(24)(25) XIII (26) RHAMM/HMMR marker expression in the same stem cell lineage obtained from various tissues may indicate differences in their pluripotency. It is also possible that stem cell marker expression pattern and levels depend on respective cell cycle phases.…”
mentioning
confidence: 99%
“…Mitsui et al 46 found high concentrations of mRNA Nanog within the morula stage during embryonic development, and likewise, Tay et al 47 found that in the absence of OCT-3/4 and LIF, Nanog is capable of maintaining a pluripotent cell. Riekstina et al 48 al. 52 and Elloul et al 53 verified the presence of the expression of mesenchymal cell markers such as CD44, CD29, CD90 and coexpression with high participation for vimentin and Ck-Pan.…”
Section: Cell Culturementioning
confidence: 99%